Moebius Syndrome: A Case Report - Priti Singh; S B Gupta; Rashmi Kumar; Rahul Agarwal; D P Singh; Divya Verma (International Journal of Medical Research and Review, 2014)
Moebius syndrome consists of congenital, complete or partial facial nerve palsy with or without paralysis of other cranial nerves (most commonly an abducens paralysis) and often associated with other malformations of the limbs and orofacial structures. In this case, a ten days old male child with moebius syndrome is presented, clinical findings are described and management aspects are discussed.